Smartphone apps as a motivating tool in English language learning - Nagaletchimee Annamalai; Muhammad Kamarul Kabilan; Deepa Soundrarajan (Universitas Pendidikan Indonesia, 2022)
Since smartphones are getting cheaper, sophisticated, and multifunctional, there are opportunities for learners to engage in more meaningful English language learning. This study employs a mixed-method research design, with the purpose of identifying the use of English language apps outside the classroom and depicting students’ English language apps use behaviour i.e. motivation from the Self-Determination Theory (SDT). The findings show that students use the apps related to grammar the most and followed by English apps related to speaking, reading and, vocabulary. Findings also reveal students in this study display three types of motivation from the perspective of SDT i.e. autonomy, competence, and relatedness. Based on the findings, a model of Pedagogical Considerations of Using Smartphone for English Language Learning (PCUSELL) is suggested. As a conclusion, the authors suggests that educators in higher educational institution educators should consider the potential of smartphone English apps in their teaching and learning activities, particularly in this new normal of teaching and learning i.e. epoch of the COVID-19 pandemic.